2011
DOI: 10.1007/s00240-011-0429-z
|View full text |Cite
|
Sign up to set email alerts
|

Chemolysis of calcium oxalate stones: study in vitro and possible clinical application

Abstract: The flow cell modeling clinical conditions have been used to study the interaction between dilute chemolytic solutions and large calcium oxalate renal stones. The stone treatment with 5% disodium ethylenediaminetetraacetate aqueous solutions or citrate buffer are found not to provide notable disruption of the samples studied. The significant improvement is reached with the mixed compositions containing both natural and synthetic chelating reagents:citrate and ethylenediaminetetraacetate ions as well as an anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The widely used drugs for preventing formation of new stones are potassium citrate or potassium/ magnesium citrate mixtures [4,6,20]. They allow to increase urinary pH, magnesium and citrate urine excretion, to bind calcium ions into soluble Ca-citrate complexes to avoid crystallization and dissolve residual fragments [21]. Our very recent study for the group of thirty COH stone formers has indicated that hypocitraturia is a frequent disorder afflicting about 90% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The widely used drugs for preventing formation of new stones are potassium citrate or potassium/ magnesium citrate mixtures [4,6,20]. They allow to increase urinary pH, magnesium and citrate urine excretion, to bind calcium ions into soluble Ca-citrate complexes to avoid crystallization and dissolve residual fragments [21]. Our very recent study for the group of thirty COH stone formers has indicated that hypocitraturia is a frequent disorder afflicting about 90% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The causes of kidney stone formation are well understood based on previous findings from studies over the past decades [13,14]. Research has shown that C, O, N, P, and Ca are major components of kidney stones, while other elements, such as Sr, Cu, Fe, Zn, Pb, Cr, and Mn, are found in trace amounts [15][16][17].…”
Section: Introductionmentioning
confidence: 99%